Androgen receptors beyond prostate cancer: an old marker as a new target - Munoz, Javier (Oncotarget, 2014)
Androgen receptors (ARs) play a critical role in the development of prostate cancer. Targeting ARs results in important salutary effects in this malignancy. Despite mounting evidence that ARs also participate in the pathogenesis and/or progression of diverse tumors, exploring the impact of hormonal manipulation of these receptors has not been widely pursued beyond prostate cancer. This review describes patterns of AR expression in a spectrum of cancers, and the potential to exploit this knowledge in the clinical therapeutic setting.